Field Notes From Jail: How Incarceration and Homelessness Impact Women's Health - Louanne P. Keenan; Cybele Angel; Rebecca Martell; Diane Pyne; Rabia Ahmed (The University of Alabama, 2022)
A multi-disciplinary team explored the journey they took with female inmates to develop a collaborative research strategy among the university, community organizations, and the correctional facility. The team consisted of academic researchers, inner city physicians, social workers, nurses, Aboriginal art therapists, Aboriginal cultural consultants, correctional healthcare administrators, and inner city chaplains from non-profit organizations. This paper describes how the team reflected on the journey to determine the impact of incarceration and/or homelessness on the health of female inmates, as they (the team) patiently waited for ethics boards and administrative approval; negotiated correctional center lockdowns; and became exhausted from trying to reconnect with women who were released from incarceration. The researchers discovered what kept them passionate about helping female inmates work through multiple hurdles that included housing, child custody, employment, probation appointments, and counseling. These administrative and operational challenges strengthened the team's resolve to support these vulnerable women.